Acanthamoeba Keratitis: Perspectives for Patients. (3rd June 2021) - Bonini, Stefano; Di Zazzo, Antonio; Varacalli, Giuseppe; Coassin, Marco
ABSTRACT: Purpose : To unveil the long-term prognosis of Acanthamoeba keratitis based on clinical presentation and timing of diagnosis to better inform patients since the first visit regarding their length of treatment, quality of life, and visual function. Methods : Retrospective observational study enrolling patients with Acanthamoeba keratitis from 1994 to 2019. Patients with a complete eye examination and medical records were analyzed. The severity of the disease, the time from onset of symptoms to the appropriate therapeutic regimen, the time until clinical resolution, visual function, and long term follow-up was evaluated. Quality of life was assessed at the last follow-up visit by means of the VFQ-25 questionnaire. Results : Thirty-five patients (40 eyes) were assessed. The overall healing time of patients with Acanthamoeba keratitis was 12.5 ± 3.5 months, while patients with a severe corneal ulcer (stage III) had a significant longer healing time (16.2 ± 3.7 months) compared to patients with stage II (7.04 ± 0.7 months) or I (7.7 ± 1.5 months; p < .05). Patients who received a prompt therapy (<30 days form symptoms onset) had a reduced healing time compared to patients with a delayed diagnosis ( p < .01). Quality of life was assessed after a mean of 11.7 ± 4.7 years and it was mildly reduced (86.6 ± 17). Patients that were diagnosed early (<30 days from onset) showed a lower reduction in quality of life than in patients that were diagnosed >30 days from onset. After resolution, 59% of the patients considered unnecessary any further proposed surgical intervention. Conclusions : Delayed diagnosis of Acanthamoeba keratitis and disease severity significantly increases healing time and duration of treatment. The time to diagnosis and disease stage at diagnosis predicts the duration of treatment, the final outcome, quality of life, and the requirement of surgery. These data would allow us to promptly inform patients about long-term disease timeline, future outcomes, improving disease acceptance, and quality of life.